Intuition Concept in Small and Medium Enterprises through Strategic Decision-Making - Wiratmadja, Iwan Inrawan; Rumanti, Augustina A.; Reynaldo, Rocky; Kurniawati, Amelia (International Review of Management and Marketing, 2017)
As one of the main economic pillars in Indonesia, small and medium enterprise (SME) has a unique characteristic of embracing environmental uncertainty and internal limitation. Previous researches defined two approaches of decision making i.e. rational and intuitive. Actual business practice shows that time limitation, combined with great amount of assessed variables, could create an inevitable tendency for leaders to develop their intuitive process in the decision-making. Research was conducted in four industries in Yogyakarta, Central Java i.e. batik, stone, pottery and food, with the goal of assessing the relation between environmental uncertainty to strategic decision-making, along with the impact in regards to SME's performance. The data was processed with partial least square based structural equation modelling. This research shows no causality between variables and provides strategic suggestions accordingly to improve performance. Keywords: SMEs, Intuition, Strategic Decision-Making JEL Classifications: C39, D81, L26